Comparison between different individuals of Bactrocera (Zeugodacus) Scutellata (Hendel) (Diptera: Tephtitidae) reveals differential mutation rates of mitochondrial genes. Issue 2 (2nd April 2020) - Zhang, Kai-Jun; Liu, Lei; Li, Guo-Yang; Hu, Wen-Zhao; Li, Ya-Ying; Tian, Chuan-Bei; Liu, Huai
Abstract: We sequenced and annotated the complete mitochondrial genome (mitogenome) of Bactrocera scutellata (Diptera: Tephritidae), which is an economically important pest in many area of East Asia. This mitogenome is 15, 850 bp in length with an A + T content of 72.99%, and contains 37 typical animal mitochondrial genes that are arranged in the same order as that of the inferred ancestral insects. All protein-coding genes (PCGs) start with a typical ATN codon, with the exception of cox1, which begins with TCG. Ten PCGs stop with termination codon TAA or TAG, whereas cox1, nad1 and nad5 have single T as the incomplete stop codon. All of the transfer RNA genes present the typical clover leaf secondary structure excepting trnS1 (AGN) without a DHU-arm. The A + T-rich region (945 bp in length with 84.66% A + T content) is located between rrnS and trnI, and contains a 20 bp poly-T stretch and 21 bp poly-A stretch. Excepting the control region, the longest intergenic spacer locates between trnR and trnN which is 56 bp long with an excessive high A + T content (89.29%). Compared with other two mitogenomes of B. scutellata revealed that the mutation rates of mitochondrial genes were quite different. For population genetic studies of this species, we recommend using the cox1 or nad5 genes.